Orientasi Kewirausahaan, Kapabilitas Pemasaran, dan Kinerja Usaha Mikro di Indonesia - Mega Noerman Ningtyas; Sudarmiatin Sudarmiatin; Agus Hermawan (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2026)
Micro-enterprises play a strategic role in Indonesia’s economy; however, the literature shows inconsistencies regarding how entrepreneurial orientation translates into business performance, particularly in micro-enterprise contexts. This study examines the mediating role of marketing capability in the relationship between entrepreneurial orientation and business performance among micro-enterprises in Indonesia. A survey of 230 micro-enterprise owners in East Java was conducted, and the data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that entrepreneurial orientation has a positive and significant effect on both marketing capability and business performance. Marketing capability also mediates the relationship between entrepreneurial orientation and performance. These findings suggest that entrepreneurial orientation does not automatically enhance performance without adequate marketing capability. Practically, the results highlight the need for policymakers, such as the Dinas Koperasi dan Usaha Mikro to prioritize strengthening marketing capabilities in micro-enterprise development programs.